EFEKTIVITAS PENGGUNAAN MEDIA SOSIAL TERHADAP PEMBELAJARAN PPKN DI SMA ISLAM JEPARA - Zainuri, Ahmad; Sukoco, Sukoco; Muryati, Sri (Journal of Democratia, 2024)
The background of this research is that education is very important in the process of life where with education we will gain additional insight that is broad and useful for living a better life. Learning outcomes are the attainment of educational goals for students who take part in the teaching and learning process which are useful as a measure of the extent to which students can master the subject matter delivered by the teacher. This classroom action research was conducted with 34 students in class XI, starting from early June to July at Jepara Islamic Vocational School. The data collection method is a student questionnaire. The technique of analyzing the data uses the pre test and post test. The conclusions obtained are the use and benefits of learning effectiveness of Civics subjects using social media as a support for student learning activities in class to be more effective and fun. Because students do not feel bored with the learning model. So that it can be predicted that in the future students will try to ask teachers of other subjects to follow a learning model that is fun, effective and easy to understand using social media.